Manfaat dan Tantangan E-Commerce Dalam Ekonomi Digital di Bidang Bisnis - Selsa Dharma Wulan (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
In helping MSMEs, businesses, entrepreneurship, and others to enter the digital economy and be able to compete with foreign countries, namely by implementing e-commerce or electronic commerce. The presence of e-commerce plays an important role in this 5.0 revolution era and the State's ability to manage e-commerce can have an impact on the nation's competitiveness. However, we still find that many businesses, MSMEs and so on are still reluctant to use e-commerce with the opinion that e-commerce is a fraudulent business and there are still many people who don't know the role and benefits of e-commerce. The type of research in this article is descriptive qualitative research with a literature review methodology. This writing explains that there are benefits and challenges to e-commerce itself. The benefit of e-commerce is that there are several online applications, making it easier for consumers to shop, so consumers don't need to come to the destination area where the shop is located. One of the challenges is how to maintain customer privacy, security and trust